2020
DOI: 10.3390/polym12122885
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of the Extrusion and Deposition Process of a Poly(lactic Acid) Strand with Fused Deposition Modeling

Abstract: In the last decade, Fused Deposition Modeling (FDM) has gained popularity for allowing the fabrication of pieces with complex shapes. The final quality of the pieces is strongly linked to the shape, size and surface finish of the strands deposited successively, which themselves depend on the printing parameters and extruded material properties. In this work, we present an experimental characterization of an extruded and deposited single strand of Poly-Lactic Acid (PLA), by means of high-speed visualization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 40 publications
5
18
0
1
Order By: Relevance
“…PLA, a partially crystalline polymer, is biodegradable (compostable) and has low melting temperature but has limited thermal stability [14]. The performance of these two materials for 3D printing has been assessed [15][16][17][18], particularly in terms of dimensional accuracy [19,20], surface roughness [21], mechanical performance [22] and emission of volatile organic compounds (VOC) [23,24]. For the 3D printing of a compact omnidirectional wheel, Rubies and Palacín [25] observed that when using 100% infill density, PLA yielded a better mechanical performance than ABS.…”
Section: Related Workmentioning
confidence: 99%
“…PLA, a partially crystalline polymer, is biodegradable (compostable) and has low melting temperature but has limited thermal stability [14]. The performance of these two materials for 3D printing has been assessed [15][16][17][18], particularly in terms of dimensional accuracy [19,20], surface roughness [21], mechanical performance [22] and emission of volatile organic compounds (VOC) [23,24]. For the 3D printing of a compact omnidirectional wheel, Rubies and Palacín [25] observed that when using 100% infill density, PLA yielded a better mechanical performance than ABS.…”
Section: Related Workmentioning
confidence: 99%
“…By performing optical microscopy measurements, Serdeczny et al [5] assessed the strand geometry found by Comminal et al [4]. Based on a volume-of-fluid method, Gosset et al [6] performed numerical simulations of strand deposition. The temperature is assumed uniform.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation for additive manufacturing (AM) of polymers represents a field of high research activity covering several approaches, such as extrusion methods [4,11,29] or selective laser sintering (SLS) of polymers [1,3,10,[22][23][24][25]28]. For an overview of additive manufacturing using polymers we refer to [5][6][7]19,27] and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the model corresponding to Equation (8) (𝜔 = 1) and the modified model from Equation(11) (𝜔 = 𝜔(𝜗)) in terms of the accumulated released heat for a given temperature field. At a fully crystallized state, the accumulated released heat matches the total energy released during the exo-thermal reaction, that is, Δh 𝛼 , indicated by the red line.…”
mentioning
confidence: 99%